Disruption of nuclear speckles reduces chromatin interactions in active compartments - Hu, Shibin (Epigenetics Chromatin, 2019)
BACKGROUND: Nuclei of eukaryotes contain various higher-order chromatin architectures and nuclear bodies (NBs), which are critical for proper nuclear functions. Recent studies showed that active chromatin regions are associated with nuclear speckles (NSs), a type of NBs involved in RNA processing. However, the functional roles of NSs in 3D genome organization remain unclear. RESULTS: Using mouse hepatocytes as the model, we knocked down SRRM2, a core protein component scaffolding NSs, and performed Hi-C experiments to examine genome-wide chromatin interactions. We found that Srrm2 depletion disrupted the NSs and changed the expression of 1282 genes. The intra-chromosomal interactions were decreased in type A (active) compartments and increased in type B (repressive) compartments. Furthermore, upon Srrm2 knockdown, the insulation of TADs was decreased specifically in active compartments, and the most significant reduction occurred in A1 sub-compartments. Interestingly, the change of intra-TAD chromatin interactions upon Srrm2 depletion was not associated with the alteration of gene expression. CONCLUSIONS: We show that disruption of NSs by Srrm2 knockdown causes a global decrease in chromatin interactions in active compartments, indicating critical functions of NSs in the organization of the 3D genome. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s13072-019-0289-2) contains supplementary material, which is available to authorized users.